Post-Admission Cognitive Therapy for a Transgender Service Member With a Recent Suicidal Crisis: A Case Study of Gender-Affirming Care. Issue 2 (May 2023) - Kauten, Rebecca L.; Carter, Sarah P.; Stivers, Max; Novak, Laura A.; Baer, Margaret M.; LaCroix, Jessica M.; Grant, Nicholas E.; Sickmann, Britt; Goldston, David B.; Soumoff, Alyssa; Ghahramanlou-Holloway, Marjan
Highlights: Transgender individuals who served in the military have disparities in suicidal risk. Case study of a transgender servicewoman participating in suicide-focused treatment. Case illustrates addressing minority stressors within suicide-focused treatment. Participant reported reduced severity of suicidal ideation and related symptoms. Abstract: While elevated suicide risk in the American military and veteran population has led to the development of targeted interventions, the increased risk of suicidal ideation and behavior among transgender and gender diverse (TGD) Service members requires that interventions address suicide risk within the context of minority stressors and gender-affirming care. This case study presents Jordan (an alias), a transgender Service member who received inpatient psychiatric treatment following a suicide attempt precipitated by distress relating to gender dysphoria, minority status, and associated stressors. Jordan completed Post-Admission Cognitive Therapy (PACT; Ghahramanlou-Holloway, Cox, & Greene, 2012), a cognitive-behavioral intervention targeting suicide risk among military personnel and dependents psychiatrically hospitalized following a suicidal crisis. Within the context of PACT, Jordan's treatment included identifying and addressing distress related to minority stressors (externalized stigma, internalized transphobia, anticipated rejection, gender concealment) using gender-affirming best practices. Marked changes in Jordan's self-report measures from baseline to follow-up, as well as qualitative changes reported by Jordan, demonstrate that she felt comfortable, safe, and ready to be discharged from the inpatient unit after completing PACT treatment and gaining exposure to the skills necessary to help prevent and/or manage future suicidal crises. Treatment implications and recommendations for addressing suicide risk within the context of gender-affirming care and prevalent minority stressors are discussed.